Echinococcosis of dogs in the North Caucasian Subjects (infrastructural, epizootological and sanitary-hygienic analysis) - S. Sh. Kabardiev; A. M. Bittirov; S. A. Aigubova; N. Kh. Gyulakhmedova (Ветеринария сегодня)
Based on the official statistics the situation of parasitic diseases in the Russian Federation is still quite unfavorable. The issues of soil contamination with Echinococcus granulosus eggs are understudied that’s why the objective of the research was to study canine echinococcosis which poses a threat to animal and human disease freedom in the North Caucasian countries. Helminthological tests of the guardian dog feces were performed in seven North Caucasian Subjects: the Stavropol Krai, the Karachay-Cherkessia Republic, the Kabardino-Balkaria Republic, Republic of North Ossetia −Alania, Republic of Ingushetia, the Chechen Republic, and the Republic of Dagestan. As a result, it was determined that the average frequency index of echinococcosis occurrence was 85.07%. The moderate fecal egg count in 1,400 samples was 22.73 ± 1.49 eggs per 10 grams of dog feces. The data obtained are indicative of the disease unfavourable situation in the Subjects and the zoonosis spread at the regional level. Helminthological tests of 14,000 soil samples from near-village pastures for contamination with tapeworm eggs, including Echinococcus granulosus, showed that the invasion rate in the Stavropol Krai was 65.80%, in Karachay-Cherkessia republic − 79.00%, in Kabardino-Balkaria − 82.60%, in North Ossetia − Alania − 74.65%, in Ingushetia − 88.20%, in Chechnya − 83.75%, in Dagestan − 79.85%. The results obtained testify to the high level of soil contamination with the infective eggs. It was demonstrated that there is a relationship between the distribution of viable Echinococcus granulosus eggs in pasture soils and ecological characteristics of the Subject: the largest number of viable Echinococcus granulosus eggs was observed in submountain areas, fewer eggs were observed in flatlands, and the least number of eggs – in the mountain areas. The number of eggs detected in the soil samples from pastures is indicative of the disease persistence in humans and animals. Results of the helminthological tests of 7,500 soil samples from 119 cattle-driving routes of the North Caucasus demonstrate 100% contamination with parasitic agents which poses a threat of epidemiological and epizootological situation of echinococcosis in the Subject.